c - 9 (b, 2019)
Autobiographical reminiscences of Salehuddin Ahmed, b. 1949, economist and college teacher from Bangladesh.
AAL
In Bengali.
Keywords: Ahmed, Salehuddin, -- 1949-; Economist -- Bangladesh -- Biography; Economics; Authors, Bangladeshi -- Biography